Modelling Of Single Photon Avalanche Diodes - Li, Tan Siew (2008)
The avalanche dynamics in single photon avalanche diodes (SPADs) in the form of GaAs p+ -i-n+ diode structures was investigated theoretically using a simple random ionisation path length (RPL) MODEL. In the RPL model, the avalanche multiplication process in the i-region of a diode is modelled by generating random carrier trajectories, which may result in impact ionisation as described by an exponentially decaying probability distribution function (PDF) of the ionisation path length following a hard-threshold dead space.